1998
DOI: 10.1002/jmri.1880080312
|View full text |Cite
|
Sign up to set email alerts
|

Variations in blood flow waveforms in stenotic renal arteries by 2D phase‐contrast cine MRI

Abstract: Waveform variations in blood flow measurements through stenotic renal arteries have been reported already with echo Doppler studies. We studied these variations with MRI in 14 patients (mean age, 60 years) with suspected renal arterial stenosis (24 patent arteries, four occluded). Flow measurements were successful in 15 arteries and unsuccessful in nine, due to practical limitations. Seven healthy younger volunteers (mean age, 28 years) and five healthy older volunteers (mean age, 58 years) were recruited for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…The most obvious differences are a lower base flow level and a less steep acceleration phase in the stenotic vessels. This is another way of expressing the differences between the groups in a and b values (or the inclusion of a and d in the final logistic regression model) and is in line with observations in earlier studies (28,30). A decreased flow in diastole with progressing disease has also been found with ultrasound in conditions such as renovascular and essential hypertension (34 -36).…”
Section: Parameter Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…The most obvious differences are a lower base flow level and a less steep acceleration phase in the stenotic vessels. This is another way of expressing the differences between the groups in a and b values (or the inclusion of a and d in the final logistic regression model) and is in line with observations in earlier studies (28,30). A decreased flow in diastole with progressing disease has also been found with ultrasound in conditions such as renovascular and essential hypertension (34 -36).…”
Section: Parameter Analysissupporting
confidence: 85%
“…Our visual impression is that a large part of the explanation lies in difficulties in delineating the cross section of the arteries rather than in inherent signal-to-noise limitation in the images. Judging from the curves in other publications (28,29), this seems to be a common problem of the phase-contrast method. This was one of our major rationales for creating an analysis method less sensitive to noise in the curves.…”
Section: Image Acquisition and Curve Calculationmentioning
confidence: 91%
“…Schoenberg et al and Westenberg et al have observed that the flow waveform in the renal artery changes as the hemodynamic significance of the stenosis changes; pulsatility of the flow waveform decreases as the stenosis becomes more hemodynamically significant. 7,8 That observation is consistent with the results of a study of pulsatility or "resistance" of the renal artery using color Doppler ultrasound. 9 In the context of that study, pulsatility or "resistance" is defined as 100 x (1 -end-diastolic velocity divided by maximal systolic velocity).…”
Section: Introductionsupporting
confidence: 78%
“…Also, the outlet diameters of the left and right renal arteries are 5 mm and 4 mm, respectively. The wall thicknesses of the aorta and renal arteries are not equal, and they are set to be 2 mm and 1 mm, respectively [19] . It has been shown that, in the renal artery of humans, the RAS commonly occurs in the upstream portion 1 cm to 2 cm distal to the renal ostium [23] .…”
Section: Geometry and Gridsmentioning
confidence: 99%
“…Kagadis et al [18] simulated the Newtonian blood flow across the rigid RAS, and investigated the effects of the RAS on the velocity, the flow rate, the overall pressure drop, and the wall shear stress. Westenberg et al [19] and Schoenberg et al [20] observed that the changes in hemodynamic significance of the stenosis can affect the blood flow waveform in the stenosed renal artery.…”
Section: Introductionmentioning
confidence: 99%